Photocatalytic Performance of ZnO: Al Films under Different Light Sources - Prashant Pradhan; Juan Carlos Alonso; Monserrat Bizarro (International Journal of Photoenergy)
ZnO and Al doped ZnO films were produced by spray pyrolysis. The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), UV-vis spectroscopy, and photoluminescence. Their photocatalytic activity was evaluated by the decomposition of the methyl orange dye using different light sources: ultraviolet light, artificial white light, and direct sunlight. The films were also tested under darkness for comparison. The ZnO films were able to degrade the test pollutant under UV and sunlight in more than a 60% after 180 min of irradiation and a scarce degradation was obtained using white light. However, the Al doped ZnO films presented a very high degradation rate not only under UV and sunlight (100% degradation), but also under white light (90% degradation after the same irradiation time). An unexpected high degradation was also obtained in the dark, which indicates that a nonphotonic process is taking place parallel to the photocatalytic process. This can be due to the extra electrons—provided by the aluminum atoms—that migrate to the surface and produce radicals favoring the decomposition process even in the dark. The high activity achieved by the ZnO: Al films under natural conditions can be potentially applied to water treatment processes.